Otolaryngology utilization of speech‐language pathology services for voice disorders. (26th August 2015) - Cohen, Seth M.; Dinan, Michaela A.; Kim, Jaewhan; Roy, Nelson
Abstract : Objectives/Hypothesis: To examine the utilization of speech‐language pathology (SLP) services by otolaryngology for outpatients with laryngeal/voice disorders. Study Design: Retrospective analysis of a large, national, administrative US claims database. Methods: The study population included patients with a laryngeal/voice disorder based on International Classification of Diseases, Ninth Revision, Clinical Modification codes from January 1, 2004 to December 31, 2008, seen by an otolaryngologist as an outpatient, and 12 months of follow‐up. Data were collected on SLP evaluation and treatment and patient factors including age, gender, geographic region, employment status, initial laryngeal diagnosis, and laryngeal diagnosis change over 12 months. Multivariable logistic regression analysis was used to investigate factors associated with receipt of SLP evaluation and treatment. Results: There were 91, 898 unique patients who met study criteria. A total of 4, 485 (4.9%) patients had an SLP evaluation, of whom 2, 216 (49.4%) had at least one voice therapy session. Patient age, gender, geographic region, and laryngeal diagnosis were associated with increased likelihood of receiving SLP services. Patients whose final laryngeal diagnosis changed from their initial diagnosis had greater odds of having an SLP evaluation (odds ratio = 1.18, 95% confidence interval = 1.06‐1.31) compared to patients without laryngeal diagnosis change. Conclusions: SLP evaluation and treatment occurred in a minority of laryngeal/voice‐disordered patients. Further study is needed to assess the impact of SLP services on the healthcare utilization of patients with laryngeal/voice disorders. Level of Evidence: 2C. Laryngoscope, 126:906–912, 2016